Factors influencing readiness of local governments in implementing government regulation in government of Riau province - Azlina, Nur; Naza, Ahrun; Julita, Julita (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
This study is to examine the factors influencing the readiness of local governments in the implementation of Government Regulation 12 of 2019 regarding regional financial management. The investigated factors include human resources competency and organizational commitment. The research applied a quantitative approach using primary data. The sample for this study consisted of 108 respondents from 27 regional work units in the government of Riau Province. The method of determining the sample by using a census sampling method. Multiple linear regression analysis was used to analyze the data with SPSS version 25.0 software. The results of this study represent that the human resources competency has a significant positive effect on the readiness in implementing regulation and then organizational commitment has a significant positive effect on the readiness in implementing regulation. The research contributions are important for local governments to strategize the effective guidelines for change to ensure the successful implementation of the regulation.